A web-based educational tool using programmable logic controller-connected MATLAB-OPC server - Aydogmus, Omur (Sage Publications Ltd, 2015)
Many technological developments contribute to the progress of the education system. Especially, engineering education is affected by the latest developments in internet technology. Therefore, the engineering education system has to keep up with developing technology by using web-based systems. This work provides a convenient method to improve students' learning outcomes, their skills and their real-time experiences in multidisciplinary engineering education such as electrical, electronics, mechatronics and control engineering. In this study, a web-based real-time laboratory system was developed by using a programmable logic controller-connected MATLAB server via object linking and embedding for process control. The developed educational tool can be accessed on internet by the currently registered students. This remote accessible real-time mechatronic system consists of a programmable logic controller-connected MATLAB server, a water level tank, a servo pneumatic actuator, a pressure transmitter and two real-time cameras. The established system provides a real-time experience for students by using real instruments accessible on internet. This developed educational tool can be used as a complementary practice for some engineering courses such as sensors and actuators, control systems and industrial automation systems.
Keywords: Engineering education; programmable logic controller; remote access lab; web-based education